2012
DOI: 10.1021/ef3004569
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Fossil Fuel Era: On the Feasibility of Sustainable Electricity Generation Using Biogas from Microalgae

Abstract: In this century, biofuels will play an important role as fossil fuel alternatives. However, the long-term sustainability of large-scale biomass-based energy production chains is largely unknown. The current study evaluates the effect of nitrogen and phosphorus nutrient recovery on net energy ratio (NER) and land use, comparing a prospective industrial-scale microalgae production system with established maize agriculture. The functional unit was the delivery of 1.0 TWh of electrical energy using biomethane firi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Ter Veld [52] found an EORI > 3 for biogas produced from microalgal biomass grown in high rate algal ponds (HRAPs) and concluded that microalgae-based biofuel sustainability was not set by areal productivity or lipid content in the algae but by the recovery of nutrients. Another energy balance model for the production of biogas from microalgae grown on wastewater found energy returns on operational energy invested greater than 3 with the use of nutrients from wastewater being a crucial component in producing a positive net energy balance [53,54].…”
Section: Introductionmentioning
confidence: 99%
“…Ter Veld [52] found an EORI > 3 for biogas produced from microalgal biomass grown in high rate algal ponds (HRAPs) and concluded that microalgae-based biofuel sustainability was not set by areal productivity or lipid content in the algae but by the recovery of nutrients. Another energy balance model for the production of biogas from microalgae grown on wastewater found energy returns on operational energy invested greater than 3 with the use of nutrients from wastewater being a crucial component in producing a positive net energy balance [53,54].…”
Section: Introductionmentioning
confidence: 99%
“…The lipid extracted microalgae biomass (LEMB) could also be anaerobically digested to obtain biogas gas (i.e., methane); the methane yield was reported in the range of 0.3-0.504 L/g of LEMB [22,105]. The energy return on operational energy invested (EROOI) for the overall process of biogas production from wastewater grown microalgal biomass could exceed 3 [213,214]. During the AD process and the conversion of methane to electricity, CO 2 would be generated, which could be integrated with the microalgal cultivation in wastewater.…”
Section: Energy Production and Nutrients Recyclingmentioning
confidence: 99%
“…Sustainable electricity generation via biogas is directly influenced by biogas production. According to research by references [13], the sustainability of biogas production is not determined by regional results but by nutritional and operational recovery factors. The raw materials for biogas generators and their availability show the potential for biogas production to be used as an alternative fuel for sustainable electricity generation.…”
Section: Introductionmentioning
confidence: 99%